Answer: m = -3
............................
The answer is 12+3r because 4 times 3=12 then the 3r which you cannot add because they are no others variables that are r
<h3>
Answer: p = 0.12*(1.02)^t</h3>
Explanation:
The general exponential growth equation is
p = A*B^t
where t is the number of years that have gone by after 2008, A is the starting amount, B is the growth multiplier, and p is the price t years after 2008
We know that A = 0.12 is the starting price
The value of B is B = 1.02 which is in the form 1+r since 1.02 = 1 + 0.02 = 1+r
The r value is r = 0.02 and it is positive to represent growth. Keep in mind that 2% = 2/100 = 0.02
So we go from
p = A*B^t
to
p = 0.12*(1.02)^t
Answer:
-456 I think but I could be wrong though